Material resiliente provisório para reembasamento de prótese dentária: relato de caso - Souza, Gildson Araujo de (2018)
The increase in life expectancy in the elderly population is a worldwide phenomenon, and accompanied by the strong presence of total edentulism. Among the options for rehabilitation of these patients are the total prosthesis, which can be mucosuported or retained through osseointegrated implants. Although solutions with dental implants are considered prosthetic options with greater satisfaction and masticatory efficiency, there is a portion of the population that opts for the use of total dentures. Both treatments, in some of the manufacturing steps, use can be made of the resilient repellents to relieve pressure under the underlying tissues. The objective of this work was to evaluate the temporary resilient material for dental prosthesis reline through a case report. This research was carried out in the Scielo and PubMed databases; using the descriptors through DeCS (dentures, Dentures, Denture Bases) and MeSH (Denture Rebasing; Denture Bases). In order to illustrate the use of the soft reliner material, the objective of the present study was to select 02 patients who needed to apply a temporary soft reliner material. The clinical stages were followed with a photographic record. It is concluded that this technique has a great clinical applicability being indicated in situations such as knife blade edges, areas of recent extraction, areas in proximity to noble structures, areas of high alveolar retentivity. The resilient materials, although presenting their disadvantages, if well indicated, collaborate with the tissue repair and adaptation of the patient to the new prosthetic base.